Introducing our series: research synthesis and meta-research in biology - Nakagawa, Shinichi (BMC Biol, 2020)
Research synthesis is the process of bringing together findings and attributes from different publications, for example, to give a more complete description of phenomena than is usually possible in a single work. We bring the Research Synthesis Series to BMC Biology to promote meta-analyses, other research syntheses including meta-research studies, and research synthesis methodologies in biology, facilitating their dissemination to broader communities.